Evaluating the effectiveness of road hump on changes in speed of vehicles at institutional road in International Islamic University Malaysia - Mustafa, Nur Asiah; Rosli, Nur Najiah Azhani; Kadar Hamsa, Abdul Azeez (Eastern Asia Society for Transportation Studies (EASTS), 2017)
This paper investigates the effects of road humps with different design profiles in reducing the speed of vehicles at the institutional road in International Islamic University Malaysia. Road humps are installed along the campus area in order to control the speed of moving vehicles as well as the driver’s behavior. Therefore, the study was conducted in order to ensure the effectiveness of road humps installation in the campus area. Field survey and spot speed survey were conducted to collect primary data for the research. The data collected were then analyzed using descriptive analysis and independent t-test. The major finding of this study entails that road hump is effective in reducing the speed of vehicles at the institutional area. The dimensions of road hump especially in height give greater influence on speed reduction of vehicles.